Preparation of CeO2 Nanoparticles by Using Mesoporous Active Carbon as Template - CHENG, TAO; FANG, ZHIYONG; HU, QIXIU; HAN, KAIDONG; YANG, XIAOZHI; ZHANG, YOUJIN (Asian Journal of Chemistry, 2010)
CeO2 nanoparticles were prepared by using mesoporous active carbon as template. The prepared CeO2 nanoparticles were cubic phase with an average size of 8 nm and narrow distributing. The results indicate that the mesoporous active carbon template plays an important role in preparing CeO2 nanoparticles.